Picosecond carrier lifetime measurements on a single GaAs Nanowire - Parkinson, P; Wang, H; Gao, Q; Tan, H; Jagadish, C (2012)
The photocarrier lifetime within semiconductor nanowires is a critical parameter for optoelectronic applications. Here, we present a technique to determine the lifetime with picosecond resolution, revealing a 7.5 ps lifetime for GaAs nanowires. © OSA 2012.